CHIVA strategy in chronic venous disease treatment: instructions for users. (April 2015) - Gianesini, S; Occhionorelli, S; Menegatti, E; Zuolo, M; Tessari, M; Spath, P; Ascanelli, S; Zamboni, P
Along the years, scientific clinical data have been collected concerning the possible saphenous flow restoration without any ablation and according with the CHIVA strategy. Moreover, in 2013 a Cochrane review highlighted the smaller recurrence risk following a CHIVA strategy rather than a saphenous stripping. Nevertheless, the saphenous sparing strategy surely remains a not-so-worldwide-spread and accepted therapeutic option, also because considered not so immediate and easy to perform. Aim of this paper is to provide an easily accessible guide to an everyday use of a saphenous sparing strategy for chronic venous disease, highlighting how even apparently too complicated reflux patterns classifications can be fastly and successfully managed and exploited for a hemodynamic correction.